Trajectories of sport exhaustion, cynicism and inadequacy among adolescent student-athletes: a three-year longitudinal study of social influences in the Finnish dual career context - Kuokkanen, J.; Phipps, D. J.; Saarinen, M.; Korhonen, J.; Romar, J.-E.; Gustafsson, H. (Psychology of Sport and Exercise, 2026)
Sport schools enhance adolescents` athletic development by offering extra training opportunities in addition to sport club training, but a rapid increase in the training load may elevate the risk of sport burnout. Thus, the aim of this study was twofold: (1) to explore the trajectories of three sport burnout dimensions (exhaustion, cynicism and inadequacy) among Finnish student-athletes (n = 268; 44 % female, 56 % male) across three academic years in lower secondary sport schools (ages 13-15 years), and to (2) examine how these trajectories were associated with student-athletes' perceived social support from parents, peers and coaches, as well as their gender, sport type and competition level. Student-athletes completed associated questionnaires at three time points at the end of three academic years—Grades 7, 8, and 9. Linear latent growth models revealed that feelings of inadequacy and cynicism increased during lower secondary school across the sample. At baseline, female student-athletes reported higher levels of inadequacy and cynicism, whereas males showed higher levels of exhaustion. Social support from peers and coaches reduced the initial levels and progression of burnout over time, respectively. Although paternal support initially minimized inadequacy, continued support subsequently tended to increase inadequacy. The findings highlight the importance of examining the three dimensions as interconnected aspects of sport burnout, and to support student-athletes in addressing emerging feelings of inadequacy and cynicism before these symptoms intensify. Educating coaches and strengthening peer support would be particularly beneficial while helping mothers to take a more active role in sports and fathers to provide support without becoming overly involved.